2011
DOI: 10.1007/s12011-011-8972-6
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Fructoborate—Potential Anti-inflammatory Agent

Abstract: Calcium fructoborate is a boron-based nutritional supplement. Its chemical structure is similar to one of the natural forms of boron such as bis-manitol, bis-sorbitol, bis-fructose, and bis-sucrose borate complexes found in edible plants. In vitro studies revealed that calcium fructoborate is a superoxide ion scavenger and anti-inflammatory agent. It may influence macrophage production of inflammatory mediators, can be beneficial for the suppression of cytokine production, and inhibits progression of endotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 94 publications
(127 reference statements)
0
63
0
Order By: Relevance
“…CF is efficient in the prevention and treatment (as adjuvant) of osteoporosis and osteoarthritis (Peng et al, 2000;Miljkovic et al, 2009;Scorei & Rotaru, 2011). In addition, CF has shown inhibitory effects on MDA-MB-231 breast cancer cells (Scorei et al, 2008;Scorei & Rotaru, 2011). CF most likely enters the cell through a co-transport mechanism via a sugar transporter (Miljkovic et al, 2009).…”
Section: Calcium Fructoboratementioning
confidence: 99%
“…CF is efficient in the prevention and treatment (as adjuvant) of osteoporosis and osteoarthritis (Peng et al, 2000;Miljkovic et al, 2009;Scorei & Rotaru, 2011). In addition, CF has shown inhibitory effects on MDA-MB-231 breast cancer cells (Scorei et al, 2008;Scorei & Rotaru, 2011). CF most likely enters the cell through a co-transport mechanism via a sugar transporter (Miljkovic et al, 2009).…”
Section: Calcium Fructoboratementioning
confidence: 99%
“…[7][8][9] CFB is a patented plant mineral compound, which is displayed and sold as bulk as a nutritional supplement under the name of FruiteX-B ® (FrxB), 10 a nature-identical analogue of a plant mineral complex with potential health benefits for conditions associated with inflammation of the bone, joint and cardiovascular system. [6][7][8][9][10][11][12] In the past, quantification of boronic/boric/borate esters has been performed using liquid and solid 11 B-NMR, 11,13,14 TLC, [15][16][17] HPLC coupled with UV or fluorometric detection, 18 thermal analysis, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Raman and inductively coupled plasma (ICP) spectroscopy 19 either alone or in combination with other compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Henderson and co-workers confirmed that a high level of boric acid in the blood reduces the risk of prostate cancer by reducing the level of Ca ++ in cells and signal transmission [33]. Scorei and co-workers demonstrated the antiproliferative effects of boric acid and calcium fructoborate (the form of boron in food) in breast cancer cells and also showed that calcium fructoborate induces apoptosis [34]. Hsu and co-workers showed that boric acid may be helpful for the treatment of bone cancers because it has cytotoxic effects and it accumulates in bones [19].…”
Section: Discussionmentioning
confidence: 98%